Penguatan Kelembagaan Dalam Meningkatkan Sektor Ekonomi Melalui Investasi - M. Widaningsih; Novianita Rulandari (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Investment services and licensing development have changed dynamically in line with global economic developments. This situation requires innovation in the investment and licensing processes in order to improve the climate of investment. Efforts can be made in various ways such as human resource development or organizational management aimed at facilitating services for the business community. Based on the latest phenomena and facts supported by the data, the issues are analyzed using a qualitative method approach and descriptive analysis method. Thus, descriptive analysis method is applied to look for facts by accurately interpreting and describing group and individual characteristics of the phenomena found from the results of this study. The results showed that the licensing bureaucracy was very long so that it could have an impact on licensing costs. This does not support the objectives of investment policies.. It can be concluded that the problem lies in the institutional aspect of Dinas Penanaman Modal dan Pelayanan Terpadu (DPMPT) is still weak in formal and informal rules and their. Thus, to create an effective institution so that it can increase investment realization, it requires adherence to formal and informal rules which have implications for the licensing process which has a certainty in terms of pressing long bureaucracy and high transaction costs.